Effect of Hydrothermal Curing on Hydration Characteristics of Metakaolin-CKD Pastes at Different Temperatures in a Closed System - Shatat, Mohamed R.; Ali, Gomaa A. M.; Gouda, Gamal A. H. (Elsevier, 2016)
Well sealed stainless steel capsule was used as a hydrothermal system to study the pozzolanic activity and hydration characteristics of metakaolin (MK)–cement kiln dust (CKD) at different temperatures (40, 80, 120 and 150 °C) up to 24 hours of hydrothermal curing. The physico-chemical properties of hydrothermally treated MK–CKD pastes were studied by measuring the compressive strength, porosity and bulk density of the hardened pastes as hydraulic properties. The hydration properties of the pastes were studied by measuring free lime and chemically-combined water contents. The phase composition and crystalline structure of the obtained hydrates were studied using X-ray diffraction (XRD) and differential thermal analysis (DTA). The results indicated that, the higher activity is shown at 80 °C especially at the later age of hydrothermal curing. Moreover, the mix containing 75% MK and 25% CKD by mass possessed the higher characteristics during the later age of hydrothermal curing and at all curing temperatures